A New Method of Measuring Financial Risk Aversion Using Hypothetical Investment Preferences: What Does It Say in the Case of Gender Differences?. Issue 4 (2nd October 2018) - Meziani, A. Seddik; Noma, Elliot
ABSTRACT: Aversion to risk is one of the main factors driving investment decisions. Studies have been based on either simple decisions in a laboratory setting or real-life decisions viewed in retrospect. The study's main contribution to the literature consists of a new and elaborate method of measuring risk combined with a real-world investment task brought into a laboratory setting and show that in this controlled environment on average women are more risk averse than men. Unlike previous studies, the authors measure risk tolerance in units that naturally map into the risk-return space used by investors, giving them the missing tool to identify the optimal portfolio among the set of investment options that comprise the efficient frontier.